Long‐ and short‐distance signaling in the regulation of lateral plant growth - Brackmann, Klaus; Greb, Thomas (Physiologia plantarum, 2014)
Lateral growth of shoot and root axes by the formation of secondary vascular tissues is an instructive example for the plasticity of plant growth processes.